Molecular evolution of type 2 porcine reproductive and respiratory syndrome viruses circulating in Vietnam from 2007 to 2015. Issue 1 (December 2016) - Do, Hai; Trinh, Dinh; Nguyen, Thi; Vu, Thi; Than, Duc; Van Lo, Thi; Yeom, Minjoo; Song, Daesub; Choe, SeEun; An, Dong-Jun; Le, Van
Abstract Background Porcine respiratory and reproductive syndrome (PRRS) virus is one of the most economically significant pathogens in the Vietnamese swine industry. ORF5, which participates in many functional processes, including virion assembly, entry of the virus into the host cell, and viral adaptation to the host immune response, has been widely used in molecular evolution and phylogeny studies. Knowing of molecular evolution of PRRSV fields strains might contribute to PRRS control in Vietnam. Results The results showed that phylogenetic analysis indicated that all strains belonged to sub-lineages 8.7 and 5.1. The nucleotide and amino acid identities between strains were 84.5–100% and 82–100%, respectively. Furthermore, the results revealed differences in nucleotide and amino acid identities between the 2 sub-lineage groups. N-glycosylation prediction identified 7 potential N-glycosylation sites and 11 glycotypes. Analyses of the GP5 sequences, revealed 7 sites under positive selective pressure and 25 under negative selective pressure. Conclusions Phylogenetic analysis based on ORF5 sequence indicated the diversity of PRRSV in Vietnam. Furthermore, the variance of N-glycosylation sites and position under selective pressure were demonstrated. This study expands existing knowledge on the genetic diversity and evolution of PRRSV in Vietnam and assists the effective strategies for PRRS vaccine development in Vietnam.